(untitled) (Bulletin of the International Association for Paleodontology, 2021)
Estimating the age at death of archaeological individuals is critical for the reconstruction of the demographic profile of past populations. Teeth are very resistant to mechanical, chemical and physical damage. Thus, dental age estimation methods have been proven remarkably useful, especially when the other available bone remains are poorly preserved. In this study, we estimated the age of subadult individuals from pre-colonial archaeological sites in the state of São Paulo, Brazil, which are under the curation of the Museum of Archaeology and Ethnology at the University of São Paulo (MAE-USP). Age estimation was based on the analysis of dental mineralization stages originally proposed by Demirjian et al. (7) and applied to third molars by Soares et al. (11). Teeth (n = 18) were radiographed on a portable X-ray device and the images were analyzed in DICOM extension. The intraexaminer reliability test showed excellent agreement regarding the classification of mineralization stages (Kappa value = 0.94). This age estimation method showed good agreement with the previously cataloged age estimates, which were used for comparison. Of the 18 teeth examined, 15 had their age correctly estimated within the comparative range and only three did not match, of which two were very close to the cataloged estimates and one was underestimated by several years. Collectively, our findings suggest this method can be accurately applied to archaeological individuals.